Devaluation, the Specie Flow Mechanism and the Steady State - Anderson, Richard K.; Takayama, Akira (Review of Economic Studies, 1977)
Richard K. Anderson, Akira Takayama; Devaluation, the Specie Flow Mechanism and the Steady State, The Review of Economic Studies, Volume 44, Issue 2, 1 Jun